Snake Oil Game - Gaming, Hasbro (Pawtucket : Hasbro, 2016)
Players put their charm, quick thinking, and persuasive personality to the test with the creative and hilarious Snake Oil game. One player is the “customer,” and the rest of the players are "salesmen" trying to convince the customer to purchase their product over the others. The products to sell are made by combining two of the Word cards, and players have to gear their sales pitch to the customer's character. Selling a snow machine to a caveman would be quite different from selling one to a rock star! Lie, fib, and make up some ridiculous stories in order to collect the most Customer cards. After each player has been the customer once, the player with the most Customer cards wins! Original Game by Jeff Ochs and Patricia Hayes Kaufman. Hasbro Gaming and all related terms are trademarks of Hasbro.
Kaartspel
Keywords: Persoonlijkheid; Gezelschapsspellen